MENDIRIKAN MUSYAWARAH GURU MATA PELAJARAN (MGMP) GEOGRAFI DI KABUPATEN PASAMAN BARAT SUMATERA BARAT - Hawariyun, Hawariyun (STKIP Pesisir Selatan, 2017)
Best practice is backgrounded by the problem of not having container of Subject Teacher (MGMP) Geography of SMA / MA in Pasaman Barat. So it is very impact on career development and PKB Geography teacher in West Pasaman District. This Best Practice contains the experience of the steps in the MGMP's Presentation and the results achieved from the MGMP Geography Educational Experience.